BIBLIOGRAPHY ON COLD REGIONS SCIENCE AND TECHNOLOGY. VOLUME XXIII. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1969)
The Bibliography on Cold Regions Science and Technology, CRREL Report 12, was first published in 1951 and is a continuing publication of the Cold Regions Bibliography Section in the Science and Technology Division of the Library of Congress. It is sponsored by and prepared for the Cold Regions Research and Engineering Laboratory (formerly Snow, Ice and Permafrost Research Establishment) of the U.S. Army Corps of Engineers. Beginning with volume 20 the title was changed to Bibliography on Snow, Ice and Frozen Ground. The present volume features another change in title, reflecting the somewhat expanded subject coverage, and especially the added emphasis on engineering. (Author) See also Report no. CRREL-12-Vol-22, AD-672 756, and CRREL-12-Vol-23-Index, AD-696 403.